2002
DOI: 10.1620/tjem.196.219
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intracerebroventricular Dopamine Administration on the Respiratory Response to Hypoxia.

Abstract: Acute hypoxia produces an increase in ventilation. When the hypoxia is sustained, the initial increase in ventilation is followed a decrease in ventilation. The precise mechanism of this decline in ventilation during sustained hypoxia is unknown. Recent studies hypothesized that the accumulation of dopamine in the central nervous system might have a major role in production of hypoxic respiratory depression. The purpose of this study was to examine whether dopamine has an effect on occurance of central ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Initially, it was believed that the heterogeneity of this response was due primarily to the state of arousal within any given species since in some animals HVD is only observed in the anesthetized state; however, in many species HVD is observed in both anesthetized/asleep and also in awake animals, calling this definition into question. For example, HVD has been observed in awake humans (155,167,350,351), awake and anesthetized cats (405), awake rats (229,382), anesthetized rats, as a decline in phrenic nerve activity (156,375), and in anesthetized rabbits (136), but is not observed in awake dogs (44, 60). Perhaps more confounding, in awake goats some groups detect HVD (120,121,229,382), while others do not (2,76,285).…”
Section: Physiological and Molecular Responses To Brief Hypoxic Exposmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, it was believed that the heterogeneity of this response was due primarily to the state of arousal within any given species since in some animals HVD is only observed in the anesthetized state; however, in many species HVD is observed in both anesthetized/asleep and also in awake animals, calling this definition into question. For example, HVD has been observed in awake humans (155,167,350,351), awake and anesthetized cats (405), awake rats (229,382), anesthetized rats, as a decline in phrenic nerve activity (156,375), and in anesthetized rabbits (136), but is not observed in awake dogs (44, 60). Perhaps more confounding, in awake goats some groups detect HVD (120,121,229,382), while others do not (2,76,285).…”
Section: Physiological and Molecular Responses To Brief Hypoxic Exposmentioning
confidence: 99%
“…Indirect support for this hypothesis comes from studies in which DA administered to awake humans or anesthetized rabbits prevents the acute HVR and STP, which in turn prevents the occurrence of HVD (62, 136). This suggests that upregulating inhibitory dopaminergic input during hypoxia opposes the excitation of the NTS mediated by excitatory inputs from the carotid body, which would in turn limit the release of glutamate at the NTS.…”
Section: Physiological and Molecular Responses To Brief Hypoxic Exposmentioning
confidence: 99%
“…Several agents can be classified in this group: (1) substances of central action: dopamine antagonists and other pharmacological agents that increase lung ventilation [54][55][56]; (2) inhibitors of carbo anhydrase [57,58], which lead to the accumulation of carbon dioxide in the blood and chemoreceptor stimulation of ventilation (Fig. (5)); mixtures of sodium and potassium salts [59] and other pharmacological agents.…”
Section: Paas That Increase Lung Ventilationmentioning
confidence: 99%
“…Artificial perfusion studies have also shown that the functioning of respiratory neurons in the brain stem is unaltered during moderate central hypoxemia (PaO 2 50 mm Hg) [9]. On the other hand, hypoxia influences the rate of synthesis or release of neurotransmitters and modulators [12,13], leading to accumulation of adenosine, dopamine and Á-aminobutyric acid in the brain [2,14,15]. Administration of long-acting analogues of adenosine, either systemically or directly into the third cerebral ventricle, decreases phrenic nerve activity in peripherally chemodenervated air breathing cats while theophylline, a specific antagonist of adenosine, prevents and reverses the decrease of phrenic activity [16] as reported by Javaheri et al [17].…”
Section: Introductionmentioning
confidence: 99%